PERUBAHAN NILAI-NILAI ADAT PERKAWINAN SUKU DAYAK KANAYATN DI KECAMATAN SADANIANG KABUPATEN MEMPAWAH - Tenniek Tenniek; Agus Sastrawan Noor; F.Y Khosmas (Universitas Tanjungpura, 2019)
AbstractThis research aimed to describe the change of values in Dayak Kanayatn custom marriage in Sadaniang district Mempawah regency. This research used qualitative method with descriptive-ethnography approach. The method used in collecting the data observation, interview and documentation. Device used in collecting data is observation guide, interview guide and documentation. According to the result of the research, the original arrangement of custom marriage are consist of several stage, such as penentuan picara, tahap barawas, nyuman poe’ pangumpur, ngikat kata, pantangan (pingit), tahap persiapan, marriage ceremony that started with makan batamak (bersanding), nasi tenung, ngadap sajiant, nasehat picara, ngadap buis bantant, macah piringk, penyerahan tingkalangk parimatant, balalak, and panganten baulangk. Changes occurred in the procession of Dayak Kanayatn custom marriage in Sadaniang district, such as additional and reduction of some custom props. Thus happened because of several factors, (1) Economic reasons from society; (2) Foreign culture influence from religion transmission that cause the society to held marriage ceremony according to their religion, hence several custom props are removed. Keywords: The change of Values, Custom Marriage, Dayak Kanayatn